Optimization of Industrial-Scale Cultivation Conditions to Enhance the Nutritional Composition of Nontoxic Cyanobacterium Leptolyngbya sp. KIOST-1 - Won-Kyu Lee; Yong-Kyun Ryu; Taeho Kim; Areumi Park; Yeon-Ji Lee; Youngdeuk Lee; Ji Hyung Kim; Chulhong Oh; Do-Hyung Kang; Woon-Yong Choi (Applied Sciences, 2023)
Leptolyngbya sp. KIOST-1 has been proposed as a candidate species for use as a protein supplement due to its high protein content and absence of cytotoxicity. The species has also garnered attention due to the photosynthetic pigments it possesses. However, limited information is available on its cultivation. Therefore, this study was conducted to identify the optimal culture medium and fundamental physiological properties of Leptolyngbya sp. KIOST-1 under various culture conditions. In this study, SOT (Society of Toxicology) medium was confirmed as the optimal culture medium for Leptolyngbya sp. KIOST-1 growth. The biomass production, protein content, and photosynthetic pigment content of Leptolyngbya sp. KIOST-1 were significantly higher in SOT medium. The use of this medium allowed for scaling up from laboratory (10 mL) to pilot (200 L) conditions and industrial-scale outdoor conditions (10,000 L), with the biomass containing over 66% protein. The phytochemical composition of Leptolyngbya sp. KIOST-1 cultured at laboratory and industrial-scales was discovered in this study. Furthermore, we observed that reducing the carbon and nitrogen sources to 1/5 of those supplied by the optimal medium did not significantly affect biomass production, and Leptolyngbya sp. KIOST-1 demonstrated favorable growth capabilities in a salinity range of 10–50 psu and at pH levels of 8.3 to 10.3. The results of this study demonstrate the suitability of Leptolyngbya sp. KIOST-1 for various industrial applications and its adaptability to large-scale cultivation.